Financial Education in the 21st Century in African continent: Challenges and Opportunities - Amana, Sarah (International Journal of Finance, 2025)
Purpose: Financial education is increasingly recognized as a critical life skill in the 21st century, given the complexity of modern financial systems and the necessity for individuals to make informed decisions regarding savings, investments, and debt management. This paper examines the challenges and opportunities associated with financial education, highlighting the role of technology, policy frameworks, and behavioral economics in shaping financial literacy outcomes. It also discusses the implications of financial education on individual well-being and economic stability. Furthermore, through comprehensive case studies and an in-depth analysis of global perspectives, this research identifies innovative solutions and policy implications to enhance financial education, contributing to the global discourse on economic resilience and individual empowerment. Methodology: The paper utilized a qualitative approach, sourcing data from textbooks, journal articles, government publications, newspapers, and other relevant academic materials. This method was chosen to capture diverse perspectives and provide a comprehensive understanding of financial education challenges and opportunities. Findings: The study delved into the historical context of financial education on the African continent, revealing a trajectory shaped by colonial influences, indigenous practices, and post-independence reforms. It became evident that financial education in Africa has long been marred by systemic exclusion and underdevelopment. Unique Contribution to Theory, Policy and Practice: Digital innovation and global financial literacy campaigns offered promising avenues to expand access and engagement. Inclusive financial systems, particularly those blending traditional and modern practices, demonstrated potential for economic empowerment. Integrating financial education into formal curricula was recognized as a sustainable approach for fostering long-term literacy and resilience. These opportunities underscored the transformative potential of financial education in addressing socio-economic disparities and empowering African communities. By leveraging these avenues, Africa can navigate its unique challenges and harness the power of financial education for a prosperous future.